The angular momentum of cosmological coronae and the inside-out growth of spiral galaxies - Pezzulli, G; Fraternali, F; Binney, J (Oxford University Press, 2017)
Massive and diffuse haloes of hot gas (coronae) are important intermediaries between cosmology and galaxy evolution, storing mass and angular momentum acquired from the cosmic web until eventual accretion on to star-forming discs. We introduce a method to reconstruct the rotation of a galactic corona, based on its angular momentum distribution (AMD). This allows us to investigate in what conditions the angular momentum acquired from tidal torques can be transferred to star-forming discs and explain observed galaxy-scale processes, such as inside-out growth and the build-up of abundance gradients. We find that a simple model of an isothermal corona with a temperature slightly smaller than virial and a cosmologically motivated AMD is in good agreement with galaxy evolution requirements, supporting hot-mode accretion as a viable driver for the evolution of spiral galaxies in a cosmological context. We predict moderately sub-centrifugal rotation close to the disc and slow rotation close to the virial radius. Motivated by the observation that the Milky Way has a relatively hot corona (T ≃ 2 × 10^6 K), we also explore models with a temperature larger than virial. To be able to drive inside-out growth, these models must be significantly affected by feedback, either mechanical (ejection of low angular momentum material) or thermal (heating of the central regions). However, the agreement with galaxy evolution constraints becomes, in these cases, only marginal, suggesting that our first and simpler model may apply to a larger fraction of galaxy evolution history.